2017
DOI: 10.1007/s12035-017-0503-9
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Quality Control and Disease: Insights into Ischemia-Reperfusion Injury

Abstract: Mitochondria are key regulators of cell fate during disease. They control cell survival via the production of ATP that fuels cellular processes and, conversely, cell death via the induction of apoptosis through release of pro-apoptotic factors such as cytochrome C. Therefore, it is essential to have stringent quality control mechanisms to ensure a healthy mitochondrial network. Quality control mechanisms are largely regulated by mitochondrial dynamics and mitophagy. The processes of mitochondrial fission (divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
221
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(230 citation statements)
references
References 214 publications
(256 reference statements)
6
221
0
3
Order By: Relevance
“…We know that the mitochondrial apoptosis pathway is the intrinsic pathway of apoptosis and involved in the development of many diseases . Increasing evidence has shown that I/R injury activates mitochondria‐mediated apoptosis as revealed as by the increased ratio of Bax/Bcl‐2 and the release of cytochrome c , leading to downstream caspase cascade . Further study showed that baicalin pretreatment inhibits mitochondrial damage‐mediated apoptosis leading to protecting against myocardial I/R injury .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We know that the mitochondrial apoptosis pathway is the intrinsic pathway of apoptosis and involved in the development of many diseases . Increasing evidence has shown that I/R injury activates mitochondria‐mediated apoptosis as revealed as by the increased ratio of Bax/Bcl‐2 and the release of cytochrome c , leading to downstream caspase cascade . Further study showed that baicalin pretreatment inhibits mitochondrial damage‐mediated apoptosis leading to protecting against myocardial I/R injury .…”
Section: Discussionmentioning
confidence: 99%
“…39 Increasing evidence has shown that I/R injury activates mitochondriamediated apoptosis as revealed as by the increased ratio of Bax/Bcl-2 and the release of cytochrome c, leading to downstream caspase cascade. 40 Further study showed that baicalin pretreatment inhibits mitochondrial damage-mediated apoptosis leading to protecting against myocardial I/R injury. 21 Similarly, in current study, we found that pretreatment with baicalin obviously alleviated H/R-induced increased expression of cytochrome c, Bax (pro-apoptotic protein) and decreased expression of Bcl-2 (anti-apoptotic protein) in H9c2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…7 In mammalian cells, classic autophagy is clarified into three types: macroautophagy, microautophagy and chaperone-mediated autophagy. [7][8][9] The processes of macroautophagy and microautophagy need to form vesicles. In macroautophagy, vesicle formation occurs in the cytosol, which is a double-membrane structure known as autophagosome.…”
Section: Mitophagymentioning
confidence: 99%
“…Ischemic stroke leads to necrotic and apoptotic cell death due to hypoxia or anoxia in brain tissues. Although cerebral reperfusion is important for salvaging ischemic brain tissue, it also results in a loss of mitochondrial function and disrupts the dynamic balance of mitochondrial gene expression, thereby reducing ATP synthesis (Anzell, Maizy, Przyklenk, & Sanderson, 2017;Crack & Taylor, 2005;Pulsinelli & Duffy, 1983). Mitochondrial DNA encodes genes related to ATP synthesis, such as Complex I (ND1, ND2, ND3, ND4, ND4L, ND5, and ND6),…”
Section: Discussionmentioning
confidence: 99%